UPAYA MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA MELALUI MEDIA INTERAKTIF BERBASIS CANVA PADA SISWA KELAS 3 SD N BATURAN 1 - Devita Sari; Rian Nurizka (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to enhance the learning interest of third-grade students at SD N Baturan 1 in the Pancasila Education subject specifically regarding the topic of diversity through the use of Canva-based interactive media. The study employs the Kemmis and McTaggart Classroom Action Research (CAR) model, conducted over two cycles with 27 student participants. Data were collected via observation, questionnaires, interviews, and documentation, and subsequently analyzed using both quantitative and qualitative descriptive methods. The results indicate that Canva-based interactive media successfully increased students' learning interest. Questionnaire scores regarding learning interest rose from 66.52% in the pre-cycle stage to 73.15% in Cycle I and 82.59% in Cycle II. Observation results also improved, rising from 33.33% in the pre-cycle stage to 81.43% by the end of Cycle II. Thus, Canva-based interactive media is effective in boosting students' learning interest in the Pancasila Education subject.